Multi-method Approach in Fulfilling Clean Water Resources for Inhabitants in A Rural Area: Preliminary Results - Aditya Pratama; Abdullah Husna; Ryan Dwi Wahyu Ardi; Yogi Adi Prasetya (Universitas Muhammadiyah Mataram, 2021)
Clean water scarcity is among the crucial issues for inhabitants at Cikakaban Village, Tasikmalaya City. The complexity of the geological and hydrogeological conditions around Cikakaban Village makes groundwater exploration quite difficult. Regionally, Cikakaban Village has low aquifer productivity and is located at the contact of two formations which are passed by a fault. Therefore, a multi-method approach should be used in water sources exploration to obtain comprehensive results. In this paper, we presented the preliminary results which consist of the detailed geological and hydrogeological conditions of Cikakaban Village and its surroundings based on direct field observations. These observations aim to know the lithology that composes the research area and its characteristics, the potential of aquifers and water resources around the research area, as well as an overview of the distribution of groundwater depth and its flow direction. Geological survey includes observation of outcrops, both lithological description and geological structure evidence. Meanwhile, hydrogeological survey includes observation wells (location plotting, measuring ground water level elevation and depth, and checking water quality), as well as observation of the other potential water resources around Cikakaban Village. It can be inferred that rocks underlying the study area have fine grain sizes, dominated by claystone and tuff. However, the presence of geological structure causes these rocks to potentially become productive aquifers. Other potential water sources around the research area are springs and intermittent rivers.